Particle Theory: A New Theory That May Reconcile General Relativity and Quantum Theory (Global Journal of Science Frontier Research, 2021)
In an attempt to reconcile General Relativity and Quantum Mechanics, Particle Theory is a concept that may try to address this issue. This theory explains the effects accurately calculated by General Relativity in an alternate and real, physical way, and is therefore an alternative to GR. The theory states that indivisible atomic particles are instead divided into even smaller particles (called "EM particles") held together by a central potential, the speed of light being the limit to their velocities. The "shedding" of these particles are responsible for the static and magnetic fields we observe. This also creates a "screening" effect that, for an atomic particle at rest, blocks about half of what this theory defines as the "true gravitational potential", which is just twice the Newtonian value (mediated by what this theory defines as "gravity particles"). When an atomic system of particles starts moving in a certain direction, the act of shedding and the internal movement decreases as the particles orient themselves in the direction of the velocity, which reduces the screening effect, where we start to observe the relativistic effects of General (and Special) Relativity.
Keywords: quantum gravity; general relativity and quantum mechanics; particle theory; alternative to general relativity